Crust–mantle interactions in Zijinshan ore field identified by zircon SIMS U–Pb age and zircon Hf–O isotopes. (26th February 2023) - Zhang, Wen-Hui; Yan, Shuai-Qi; Wang, Li-Yuan
Abstract: This study presents zircon U–Pb geochronology and Hf and O isotope data for granitic rocks in the Zijinshan ore field, southwestern Fujian Province, China. The intrusive rocks comprise monzogranite, granite and granodiorite. The magmatic zircon U–Pb ages from these granitic rocks can be divided into four episodes: episodes 1 (157.9–159.9 Ma) and 2 (141 Ma) in the Late Jurassic and episodes 3 (108.1–103.2 Ma) and 4 (97.5–99.7 Ma) in the Middle and Late Cretaceous, respectively. Patterns of rare-earth elements (REE) show enrichment in light REE and obvious negative Eu anomalies. These rocks are also enriched in Rb, Th, U, La, Ce, Nd and Hf, and depleted in Ba, Nb, Sr, P and Ti. The increasing La/Yb ratio and decreasing heavy REE content with decreasing age may imply an increasing contribution of mantle-derived materials from the Late Jurassic to Cretaceous. The zircon ϵ Hf ( t ) and δ 18 O values, ranging from −37.7 to −2.8 and 12.0 ‰ to 6.3 ‰, respectively, indicate that the lower crust is an important source of granitic rocks. There was a significant increase in ϵ Hf ( t ) values and a decrease in δ 18 O values in the younger magmatic episodes (3 and 4), which ranged from −11.4 to −0.6 and 10.7 to 6.3 ‰, respectively. This suggests an increasing contribution of mantle-derived magma to the crustal melts from the Late Jurassic to late Early Cretaceous in response to the changing regional tectonic setting from compression to extension and an increasing interaction between the crust and mantle.